(untitled) (Heritage, 2022)
The paper deals with the analysis of external and internal influences on the emergence of various forms of collective emotions in Serbia in the last thirty years. Dominique Moïsi believes that cultures of fear, humiliation and hope dominate in certain countries and regions in the present, and characterize them during the past historical periods. Individuals and groups have their own interests, motives and needs. They undertake certain activities and methods that influence political behavior, where cultures of fear, humiliation and hope can have a decisive impact on the current economic situation of the country and its role in international relations, as well as on the future of their economic development and overall social progress, relations with other states and civilizations. Among the methods of action, the methods of cooperation and the methods of conflict stand out.